An evaluation of peripheral arterial tonometry for the diagnosis of obstructive sleep apnea - Özergin Coşkun, Zerrin; Dursun, Engin; Şahin, Ünal; Çelebi Erdivanlı, Özlem; Terzi, Suat; Çeliker, Metin; Demirci, Münir (ENT Updates, 2018)
Objective: Peripheral arterial tonometry (PAT) as a portable method of monitoring sleep quality is a relatively recent innovation. The aim was to compare the results of PAT and polysomnography (PSG) and to evaluate the role of PAT in diagnosing obstructive sleep apnea syndrome (OSAS). Methods: This study included adult patients who admitted to ENT clinic with OSAS complaints (excessive daytime sleepiness, snoring, and witnessed apnea), undergone sleep monitorization using PAT system (WatchPAT 200TM; Itamar Medical Ltd., Caesarea, Israel) and had single-blind, level 1 polysomnography at sleep laboratory of Chest Diseases Department. Results: For the two sleep monitoring sessions as conducted at different times: the apnea-hypopnea index (AHI) and respiratory disturbance index (RDI) values were strongly correlated between sessions (r=0.749, r=0.753; p<0.001). The oxygen desaturation index (ODI) values were very strongly correlated (r=0.861; p<0.001). When the AHI scores calculated using PAT for the patients enrolled in the trial were taken into consideration; 89.7% of the patients were correctly diagnosed with OSAS (AHI≥5); for RDI calculated (RDI≥5) using PAT, 100% of OSAS diagnoses were correct; for AHI values calculated with the PAT method, taking 15 as cut-off point, the sensitivity was found to be at an extremely high level of 96.1%. Conclusion: PAT and PSG values were highly correlated. This finding demonstrated that the reproducibility of the results obtained with PAT was also high. This study shows that PAT can be used as a screening test for OSAS and in a group of patients who are highly suspected for OSAS.